2022
DOI: 10.1186/s13019-022-01811-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Ulinastatin on postoperative course in cardiopulmonary bypass patients in Asia: a meta-analysis of randomized controlled trials

Abstract: Objectives To evaluate the effect of urinary trypsin inhibitor (UTI) or Ulinastatin on postoperative course and clinical outcomes in patients with cardiopulmonary bypass. Methods We searched PubMed, Embase, Web of Science, and Cochrane Library for the keywords UTI and Cardiopulmonary bypass (CPB). The primary outcome measure was the intensive care unit length of stay (ICU LOS), and results were stratified for relevant subgroups (dosage of UTI). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…Nevertheless, the survival rate after 10 years of follow-up did not differ significantly between the two groups. It was consistent with a previous meta-analysis, which demonstrated that ulinastatin could reduce inflammatory cytokines but did not affect hospital mortality [35]. Generally, patients with AKI have a poor prognosis, which can lead to chronic kidney disease.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, the survival rate after 10 years of follow-up did not differ significantly between the two groups. It was consistent with a previous meta-analysis, which demonstrated that ulinastatin could reduce inflammatory cytokines but did not affect hospital mortality [35]. Generally, patients with AKI have a poor prognosis, which can lead to chronic kidney disease.…”
Section: Discussionsupporting
confidence: 92%
“…With its potential antiin ammatory effect, UTI has been used to treat a variety of diseases. For example, UTI can regulate innate immunity and proin ammatory response [19][20][21], and has been used to treat septicemia [22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…8 Recent evidence has demonstrated that ulinastatin can reduce pulmonary injury, improve pulmonary function, 9 and improve intensive care unit length of stay in cardiopulmonary bypass patients. 10 However, little is known regarding whether distinct inflammatory subphenotypes exist in ATAAD patients and respond differently to pharmacotherapies.…”
mentioning
confidence: 99%